Antifungal mode of action studies of an antimicrobial peptide, Os, in planktonic Candida albicans (ATCC 90028) - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2020)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2020.